Os limites à revisão do auto de infração no consencioso administrativo tributário - Campilongo, Paulo Antonio Fernandes (2005)
The present essay has the purpose of studying the legal system limits for review by the Public Administration of the administrative act-rule of tax assessment/tax notice. The tax assessment, being strictly an administrative act, is, at the same time, an individual, concrete rule of law. From this standpoint, and considering that the legal system comprises valid rules of law within given time and space frames, we may say that the concepts of rule of law and validity are grounds for understanding the phenomenon of production and expulsion of valid rules of law from the system. Thus, we may conclude that the phenomenon of continuous transformation of rules of law is captured by the dynamic law system. Rules are created, expelled or replaced with effective ones. Revocation is the way the law has to eject valid rules from the system by editing another valid rule, which may have the function of mere invalidation of the previous rule or the replacement thereof. The review of tax assessment/tax notice, within this context, represents the modality of revocation by replacement. In other words, the administrative act of reviewing the tax assessment/tax notice performs a double role in the system: removing the validity of the previous rule and constituting a new rule incompatible with it, since it will have other formal or material enunciations. Thus, when we analyze the assessment review in the adversary administrative proceeding, we can see that the legality principle favors the review of vicious tax administrative acts. On the other hand, the principle of legal safety presupposes the stabilization of legal relations originating from concrete, individual acts, thus inhibiting the possibility of unlimited review of the tax notice. Based on these two factors legal safety in taxation and objective legality in the tax subject matter the so-called adjective, objective and time limits have been built, which regulate the administrative reviewing activity of administrative tax-nature acts.